An Exploratory Analysis of U.S. Academically Intensive Charter Schools (AICS) - Robert Maranto; Jamison White; Sean Woytek (Education Sciences)
Considerable amounts of research have discussed “No Excuses” charter schools preparing traditionally disadvantaged students for higher education. Yet, no scholarly work has identified or investigated U.S. academically intensive charter schools (AICS) that were founded to enable students to excel academically as much as their abilities and efforts allow. Here, we offer an exploratory study of AICS, defining them, describing the lived experience of an AICS principal, presenting the first national data comparing AICS campus and student characteristics to those of other charter schools, and assessing whether, nationally, AICS succeed on their own terms, with relatively high academic achievements. The data indicate that AICS resemble other charter schools in terms of measurable campus and student characteristics. Standardized, NAEP-adjusted Z-scores reveal that AICS consistently outperform other charter and district schools in literacy and mathematics across demographic groups, with differences expanding after the COVID-19 pandemic. We end with limitations and suggestions for future research.